BERBAHASA GLOBAL, BERJUALAN LOKAL: STUDI TENTANG PERAN BAHASA INGGRIS DALAM MENINGKATKAN KREDIBILITAS MEREK DALAM PEMASARAN INFLUENCER INDONESIA - Anastasia Imelda Sayd; Hamzah Nazarudin; Irience Rachel Agatha Manongga (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: In the context of globalization, the use of English by Indonesian influencers in promoting local brands has become a common strategy, as it conveys a modern and international image while enhancing the brand’s professionalism, appeal, and perceived quality among consumers from diverse cultural backgrounds. However, the inappropriate or inaccurate use of English that does not align with the target audience may lead to misunderstandings, damage brand image, and reduce consumer trust and engagement. Therefore, the effectiveness of English in enhancing brand credibility through influencer marketing remains an important issue that requires further investigation. This study aims to describe the forms of English usage in the marketing content of local brand products by Indonesian influencers on social media and to examine consumers’ perceptions and trust toward brands based on the language used by influencers.Methods: The study employed a mixed-method approach, combining quantitative and qualitative methods. Data were collected through observation, documentation, and an online survey using a questionnaire as the research instrument. Data analysis was conducted using both qualitative and quantitative techniques.Results: The findings indicate that English is predominantly used through code-mixing and code-switching within an informal language style. From the audience’s perspective, the use of English is perceived to enhance the dimensions of brand expertise and attractiveness, while its influence on the trust dimension remains moderate.Conclusion and suggestion: These results suggest that English functions as a symbolic cue of professionalism and modernity rather than as a sole determinant of brand credibility. This study contributes to interdisciplinary discussions in linguistics, marketing, and consumer behavior within the context of local digital marketing practices. Keywords: Brand Credibility, English Language, Influencer Marketing, Local Brands